PERAN PENDAMPING SOSIAL PROGRAM KELUARGA HARAPAN DALAM MENCAPAI GRADUASI MANDIRI KPM PKH DI DESA MEKARJAYA KECAMATAN SUMEDANG UTARA KABUPATEN SUMEDANG - Nurhayati, Evi (Politeknik Kesejahteraan Sosial Bandung, 2024)
Poverty is complex and affects various aspects of life. One of the government’s efforts to overcome poverty is through the Family Hope Program (PKH). PKH aims to reduce poverty rates by involving professional workers as social assistants. The role of social assistants is very much needed in efforts to improve the welfare of PKH KPM, but in Mekarjaya Village there have been no KPMs whohave successfully graduated independently. This study aims todescribe the role of social assistants in achieving independent graduation. The research method used is descriptive qualitative. Sampling was carried out using purposive sampling techniques. Data collection techniques used were interviews and documentationstudies. After the data was collected, data validation was carriedout using triangulation techniques. Data analysis techniques were carried out both before and after data collection in the field whichincluded data reduction, data presentation, and drawingconclusions. The results of the study showed that there were three roles that were carried out quite well, the first role as a motivator, social assistants provide motivation in Family Capacity BuildingMeeting (P2K2) activities and home visits, the second role as aneducator through the delivery of all modules in P2K2, the third role as a facilitator by facilitating KPM in P2K2 activities to listen, respond, and provide space for KPM to participate in each meeting. Other roles, namely accelerator of change, liaison, social planner, mediator, and advocate have not been carried out optimally. This is because the assignment period is relatively short so that they do not understand all the needs and characteristics of KPM. In addition tothe transfer of work areas, the burden of assisting two village areas is one of the contributing factors. Furthermore, the dependence of KPM on PKH social assistance and the target of independent graduation are challenges for social assistants.